PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING PADA STANDAR KOMPETENSI MELAKUKAN PEKERJAAN DENGAN MESIN BUBUT UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS XI TP 1 SMK MURNI 1 SURAKARTA TAHUN PELAJARAN 2013/2014 - Ikhwani, Rizal Nur (Jurnal Nosel, 2015)
The aim of this research is: (1) to improve student?s activity by applying Quantum Teaching model and Mind Mapping method for teaching standard competence of working with lathe machine at class XI TP 1 SMK Murni 1 Surakarta in 2013/2014 academic year, (2) to improve student?s achievement by applying Quantum Teaching model and Mind Mapping method for teaching standard competence of working with lathe machine at class XI TP 1 SMK Murni 1 Surakarta in 2013/2014 academic year. This research was Classroom Action Research. The subject was class XI TP 1 SMK Murni 1 Surakarta in 2013/2014 academic year which consist of 27 students. This research was applied to teach standard competence of working with lathe machine. This research was conducted in two cycles. In every cycle, there were four stages: (1) planning, (2) action, (3) observation, and (4) reflection. Data was taken using observation sheets, interviews, test, and documentation. The validity of data was using triangulation. The validity of instrument was using the validity of construct and content. The quantitative data was processed by using descriptive percentage. The data from the observation was analyzed to describe student?s and teacher?s activity during the learning process. The result of this research showed that by applying the Quantum Teaching model and Mind Mapping method can improve student?s activity and achievement. Before applying Quantum teaching, student?s activity in pre-cycle (26,3%). After applying Quantum Teaching student?s activity in cycle I (65,6%) and in cycle II (83%). Student?s mastery in pre-cycle (14,81%), cycle I (51,9%) and cycle II (81,5%). Student?s average score in pre-cycle (48,81), cycle I (68,6) and cycle II (78,9). The conclusion of this research is by applying the Quantum Teaching model and Mind Mapping method improve student?s activity and achievement in standard competence of working with lathe machine at class XI TP 1 SMK Murni 1 Surakarta in 2013/2014 academic year.